How to do your research project a guide for students - Thomas, Gary, 1950- (SAGE, 2023)
Now in its fourth edition, this book provides easy to follow advice to navigate every step of your research project, from choosing your research question, deciding on your research design and methodology, collecting and analyzing your data, and writing up the finished project. Presenting a clear and detailed roadmap so you don't miss a step, the book includes: * Case studies and real-life examples so you can learn from researchers who have been in your shoes * DIY activities so you can practice your skills * Practical advice on how to organise and polish your writing and build strong arguments * Guidance and examples of how to assess ethical risk"--